(untitled) (Media Kesehatan Masyarakat Indonesia, 2019)
Hypertension and Diabetes Mellitus (DM) are increasingly prevalent and the main cause of death in Indonesia, this also happened in Jambi. The environmental and social transition that occurred in Anak Dalam Ethnic Group in Nyogan Village since 2004 has resulted to lifestyle changes and has an impact on changing patterns of disease. The purpose of this study was to determine risk factors related to hypertension and DM in SAD Nyogan Village. The research design was cross sectional used a total sample of 193 SAD, aged ≥18 years-old, living in the SAD residential area of Nyogan Village. Time of data collection during April 2019. Research variables were age, gender, family history, diet, smoking and physical activity obtained by interviews, blood pressure measurements and glucose checks. Data analysis using chi-square and multiple logistic regression. The study found the prevalence of hypertension in SAD 4,32% and DM were 0,72%. Risk factors of hypertension were age and diet, while DM were age, sex, family history, diet and physical activity. The most dominant factor related to hypertension was age (Odds Ratio (OR=4,632; 95% Confidence Interval (CI)=1,579-13,675) and the most dominant factor of DM was a diet (OR=11,23; 95% CI=0,84-150,57). The SAD needs to regulate their diet, especially when they are >40 years-old and also carry out a healthy lifestyle.